Role of globalziation defining the incidence of entrepreneurship. - Saleem Ahmad; Noman Arshed; Sultan Salem; Yousaf Ali Khan; Kamran Hameed; Sanda Kam (PLoS ONE, 2022)
Globalization boosts the process of market predictions in the pursuit of economic growth. When economic, political, and social forces gain traction by promoting policies and the climate favoring globalization, entrepreneurial results reach out. Policymakers are still searching for a context within which regional policies can be structured to foster long-term entrepreneurship opportunities. The literature on entrepreneurial phenomena is incomplete and uncertain as to how globalization forces establish a nonlinear mechanism to promote the entrepreneurial process. This study provides the basic context for identifying globalization forces to create a nonlinear effect on the entrepreneurial process in order to address this problem. The results propose that policymakers strengthen the social and political dimension of globalization to increase opportunities-based entrepreneurship.